Reducing Outdated Solution To Drive Destination Loyalty Based On Destination Image And Destination Congruence: An Empirical Investigation - Idah Kusuma Dewi; Sukrisno Sukrisno; Pranoto Pranoto; Sarrah Jessica Hidayat (UNIVED Press, 2025)
This study aims to build a new conceptual model that aims to provide an explanation of a tourism marketing destination, in this case the destination loyalty concept. The conceptual model was built with the aim of creating a bridge to overcome the gap between the Destination service cave quality variables on Destination royalties and information service on destinations. The data taken in this study used data from the Convenience sample. The data was collected from a population of both domestic and foreign tourists visiting destinations in Central Java province and the data was analyzed using the 25 Amos software. Research deserves to be accepted. This study provides evidence that the application of service dominant logic theory and self-concruity theory has become an optimal solution to increase destination loyalty based on the variables proposed from this theory. Companies are expected to provide service providers who are able to encourage positive emotions which are expected to be able to build an alignment. In addition, a destination plan that has a form of consideration in making a hard cape and soft cape. Later it will be able to encourage the emergence of a Destination which can comprehensively lead to an increase in Destination loyalty.